Molecular insights into evolution, mutations and receptor-binding specificity of influenza A and B viruses from outpatients and hospitalized patients in Singapore - Ivan, Fransiskus Xaverius (2020)
Background: This study compared the genomes of influenza viruses that caused mild infections among outpatients and severe infections among hospitalized patients in Singapore, and characterized their molecular evolution and receptor-binding specificity. Methods: The complete genomes of influenza A/H1N1, A/H3N2 and B viruses that caused mild infections among outpatients and severe infections among inpatients in Singapore during 2012–2015 were sequenced and characterized. Using various bioinformatics approaches, we elucidated their evolutionary, mutational and structural patterns against the background of global and vaccine strains. Results: The phylogenetic trees of the 8 gene segments revealed that the outpatient and inpatient strains overlapped with representative global and vaccine strains. We observed a cluster of inpatients with A/H3N2 strains that were closely related to vaccine strain A/Texas/50/2012(H3N2). Several protein sites could accurately discriminate between outpatient versus inpatient strains, with site 221 in neuraminidase (NA) achieving the highest accuracy for A/H3N2. Interestingly, amino acid residues of inpatient but not outpatient isolates at those sites generally matched the corresponding residues in vaccine strains, except at site 145 of hemagglutinin (HA). This would be especially relevant for future surveillance of A/H3N2 strains in relation to their antigenicity and virulence. Furthermore, we observed a trend in which the HA proteins of influenza A/H3N2 and A/H1N1 exhibited enhanced ability to bind both avian and human host cell receptors. In contrast, the binding ability to each receptor was relatively stable for the HA of influenza B. Conclusions: Overall, our findings extend our understanding of the molecular and structural evolution of influenza virus strains in Singapore within the global context of these dynamic viruses.